Planting Date and Genotype Effect On Morpho-agronomic Traits of Burkina Faso Sweet Grain Sorghum - Tondé, Wendmanegda Hermann; Sawadogo, Mahamadou; Yaméogo, Irissa; Tiendrébéogo, Kouka Fidèle; Kiébré, Mariam; Sawadogo, Pingawindé; Boro, Oumar; Tiendrébéogo, Josiane; Sawadogo, Nerbéwendé (Plant Science Today, 2023)
Sweet grain sorghum is an under-exploited crop mainly grown around dwelling houses. Its production faces harsh environmental conditions. This study aims to assess sowing date effect on morpho-agronomical traits of sweet grain sorghum. Thus, 30 genotypes of sweet grain sorghum were assessed under 2 planting dates (June 26 and July 20) 24 days apart in a Randomized Complete Block Designs with 3 replications using 10 traits. The results showed a significant effect of sowing date on most of the traits, except internode length. All genotypes were sensitive to photoperiod variation by reducing their sowing-flowering cycle from 08 to 20 days, size and yield at the second planting date. Delayed sowing also resulted in a decrease in plant height (66.4 cm), 100 grain weight (8.3%), panicle weight (16.84%) and grain yield per plant (18.93%). The genotypes expressed a differential sensitivity to photoperiod variation with a mean coefficient of 0.59. Finally, a clustered flowering of all genotypes between September 11 and 27 was observed for both sowing dates. These results could be exploited by sweet sorghum breeding programme in the definition of the cropping calendar.